Lived religion : conceptual, empirical and practical-theological approaches : essays in honor of Hans-Günter Heimbrock - Dinter, Astrid, 1969-; Heimbrock, Hans-Günter, 1948-; Streib, Heinz, 1951-; Söderblom, Kerstin. (Religious Studies, Theology and Philosophy E-Books Online, Collection 2008, ISBN: 9789004223080., 2008)
Lived religion' signifies a shift of focus in order to attend to the religiosity of individuals and groups as embedded in the contexts of life-worlds. It suggests fresh attention to the body, to perception, to experience, to everyday life, and to biography. The essays in this collection gravitate around the concept of 'lived religion', honoring the contributions of Hans-Günter Heimbrock , in which he suggests this conceptual framework for understanding practical theology and religious education and for designing empirical research in theology. The contributions embrace a broad spectrum and include empirical studies, exegetical and historical investigations, contributions on practical theology as well as on the theory and practice of religious education, inviting further reflection and discussion about 'lived religion.'